PENERAPAN MODEL PEMBELAJARAN CTL UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IIIA SD NEGERI 015 GURUN PANJANG KECAMATAN BUKIT KAPUR - Sinaga, Lertianna Sinaga; Marhadi, Hendri Marhadi; witri, Gustimal witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. The problem in this study is the result of the low grade social studiesstudents class IIIA SD Negeri 015 Gurun Panjang Kecamatan Bukit Kapur Average value of the initial score of 64,41. This study aims to improve student learning outcomes in social studies class IIIA SD Negeri 015 Gurun Panjang Kecamatan Bukit Kapur throught the â Aplication Model Learning Contextual Teaching Learning (CTL). Dta collection instruments in this essay is a test sheet student learning outcomes and teacher observation and student aktivities. This study was conducted from April to May 2014 were carried out by second cycles. The subject of this research is class IIIA SD Negeri 015 Gurun Panjang Kecamatan Bukit Kapur consisting 24 students. Activities teacher firs cycle first meeting with the percentage of 57,14% with less categories, the first cycle of second meeting of the percentage of 63,28% with enough categories.then the second of cycle of the first meeting with the percentage of 71,42% in both categories, the second meeting of the second cycle percentage 85,71% with very good categories. While the activity of the first cycle of student I enconter a percentage of 50% less categoriy, the first cycle of the second meeting with the percentage of 57,14% is quite categories, the first meeting of thesecond cycle of 78,57% either category, the second meeting of the second cycle percentage 82,14% with very good category. Average lerning outcomes in the first cycle and the second cycle is 70,20 in creased to 78,33 of scores to UH basis I have increased the percentage of 7,32% and the last on the basis of the UH II score increased to 19,85%. Classical completeness reaches 95% of the otherwise completed. From these results it can be concluded that the aplication of Contextual Teaching Learning (CTL) can improve IPS learning outcomes at the grade IIIA SD Negeri 015 Gurun Panjang Kecamatan Bukit Kapur. Key Words: Model Lerning Contextual Teaching Learning (CTL), the result of social studies